PENGARUH BRAND IMAGE, BRAND TRUST DAN PRODUCT QUALITY TERHADAP BRAND LOYALTY (Pada Pengguna Smartphone Samsung di FEB Universitas Islam Malang) - Mochamad Rosul; Rois Arifin; Muhammad Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this study is to determine the effect of brand image, brand trust and product quality variables on brand loyalty on Samsung smartphone users. The research method used is quantitative. The population and samples used in this research are students Faculty Economics and Business of Islamic University of Malang. The sample in this research using purposive sampling technique, while the data analysis method used in this research is multiple linear regression analysis.The results of this study provide empirical evidence that the variable brand image, brand trust and product quality both simultaneously and partially have a positive and significant impact on brand loyalty.